THE EFFECT OF WORK MOTIVATION AND WORK DISCIPLINE ON EMPLOYEE PERFORMANCE MODERATED BY ORGANIZATIONAL CULTURE ON PRIMARY KPRI PKPRI MEMBERS, SEMARANG CITY: Ari Dwi Astono1, Anis Turmudhi2, Sekolah Tinggi Ilmu Ekonomi Totalwin Semarang1,2 Jl. Gedongsongo Raya No.12 Manyaran, Semarang aridwi@stietotalwin.ac.id1, anis@stietotalwin.ac.id2 - Astono, Ari Dwi; Turmudhi, Anis (Sekolah tinggi ilmu ekonomi pemuda, 2021)
Employee performance is one of the determinants of achieving a goal expected by a company. Employee performance is influenced by several factors, including individual factors such as work discipline, work motivation and performance abilities, work experience. Also external environmental factors and internal environmental factors of the organization. Employee performance at the Primary KPRI Members of the PKPRI Semarang city is still not optimal, there are some employees who are less professional and disciplined who are not maximal. Based on these considerations, this study takes variables from individual factors, namely work motivation and work discipline. The results showed that work motivation has a positive and significant effect on employee performance (H1 accepted). Work discipline has a positive and significant effect on employee performance (H2 accepted). Work motivation has a positive effect on employee performance by moderating organizational culture (H3 accepted). And work discipline has a positive effect on employee performance by moderating organizational culture (H4 accepted).